ANALYSIS AND CALCULATION OF VOLTAGE CONTROLLED GENERATORS ON FAST-OPERATING OPERATING AMPLIFIERS - Уланський B. B.; Мачалін, І. О.; Ткаліч, О. П. (Proceedings of National Aviation University (archive), 2021)
Operational amplifiers are considered as voltage-controlled generators, which are a practical alternative to voltage-controlled transistor generators that increase in size during assembly. It is shown that operational amplifiers, as voltage-controlled generators, use the topology of the Hartley and Kolpitsa circuit and require a minimum of space, since the operational amplifier is a stick-finished impeller.